Families - Roalf, Peggy (New York, N.Y. : Hyperion Books for Children, 1992)
Presents 2000 years of art history through a series of family portraits and paintings of family scenes.
"A Jacques Lowe Visual Arts projects book"--T.p. verso.
Includes index.
Wilson's Children
Elementary School Library Collection
School Library Journal
7.1
Keywords: Family in art -- Juvenile literature; Painting -- Juvenile literature; Family in art; Painting -- History; Art appreciation; Family in art; Painting -- History; Art appreciation